The State and its International Role: Construction, Institutionalization and Change. The case of Canada's Peacekeeping Policy in Africa. - (:unkn) unknown (My University, 2008)
The end of the "Cold war" paved the way for a radical shift in Canada' peacekeeping policy. Drawing both on social constructivism in international relations and on neo-institutionalist analysis of public policy, the thesis aims at identifying the possibilities of role change in the foreign policy of states. Peace keeping is historically constitutive of Canada's political identity, which was translated into the institutionalization of a certain role for Canada on the international stage. Canadian peacekeeping practice has been deeply affected by the experiences of the Canadian diplomats and militaries in Africa, especially in the African Great Lakes (1993-2003). These experiments have nurtured a learning process, resulting in a redefinition of Canada's role on the international scene, while opening new spaces of opportunity for Canadian policy-makers. During the 2000's, Canada's peacekeeping policy evolved towards selectivity and specialization. This evolution gives us an insight on the way state actors redefine and reconfigure their roles on the international stage. The concept of role allows us to show the close relationship between the institutional structures of the social space constituted by the international system and the agents'strategies within that space.
Keywords: African Research